Chronic renal dysfunction, proteinuria, and risk of Parkinson's disease in the elderly. Issue 8 (25th April 2019) - Nam, Ga Eun; Kim, Nan Hee; Han, Kyungdo; Choi, Kyung Mook; Chung, Hye Soo; Kim, Jin Wook; Han, Byoungduck; Cho, Sung Jung; Jung, Seung Jin; Yu, Ji Hee; Park, Yong Gyu; Kim, Seon Mee
Abstract: Background: The roles of chronic kidney disease and proteinuria in the development of Parkinson's disease have not been widely studied. The objective of this study was to examine the associations of chronic renal dysfunction and proteinuria with the risk of PD in older adults using cohort data of the whole South Korean population. Methods: We included 3, 580, 435 individuals aged ≥65 years who had undergone health checkups provided by the National Health Insurance Service of South Korea between 2009 and 2012 and were followed until 2015. Multivariable Cox proportional hazards regression models were performed. Results: During a mean follow‐up of 5.2 ± 1.3 years, 30, 813 individuals (0.86% of the total population) developed PD. Lower estimated glomerular filtration rate and a higher degree of proteinuria on a dipstick test were associated with higher incidence probability of PD (log‐rank P < 0.001). In Cox regression models, chronic renal dysfunction graded by estimated glomerular filtration rate (mL/min/1.73 m 2 ) was associated with increased risk of PD after adjusting for potential confounding variables; hazard ratio (95% confidence interval) was 1.13 (1.10–1.17) for estimated glomerular filtration rate 60–90, 1.36 (1.31–1.42) for estimated glomerular filtration rate 30–60, and 1.47 (1.32–1.63) for estimated glomerular filtration rate <30 ( P for trend <0.001). Proteinuria ≥1+ was also associated with increased risk of PD development (hazard ratio, 1.12; 95% confidence interval, 1.06–1.18). Coexistence of chronic kidney disease and proteinuria showed an increased hazard ratio of 1.33 (95% confidence interval, 1.23–1.45) for PD occurrence. Conclusions: Our findings suggest that chronic renal dysfunction and dipstick‐positive proteinuria may be independent risk factors for the development of PD in older adults. © 2019 International Parkinson and Movement Disorder Society